EU-UK Relations after the War in Ukraine: Options to Re-Engage Post-Brexit - Fabbrini, Federico (Zenodo, 2024)
The article examines the relationship between the UK and the EU after Russia’s aggression ofUkraine, discussing options to deepen cooperation post-Brexit. The article outlines the current framework of EU-UK relations, emphasizing the limited partnership in place today under the Trade & Cooperation Agreement (TCA). It then highlights the possibilities offered by the TCA review, mandated in 2026, to expand bilateral relations. Moreover, the article maps broader developments occurring in the European institutional landscape following the war in Ukraine, including the establishment of the European Political Community and the renewal of the North Atlantic TreatyOrganization and the Council of Europe, and discusses how they create new opportunities for the UK to reconnect with the EU. Finally, the article considers how transformations in the EU constitutional framework, and the process of enlargement to Ukraine, impact on European integration, with possible consequences for the position of the UK.